Detection of hypoxemia and hyperoxemia by pulse oximetry in neonates and children - Sri Murni A. Ritonga; Ekawati Lutfia Haksari; Purnomo Suryantoro (Paediatrica Indonesiana, 2008)
Objective To assess the validity of pulse oximetry for detectinghypoxemia and hyperoxemia in neonates and children.Methods This was a diagnostic test study conducted in NeonatalIntensive Care Unit (NICU). The subjects of the study wereneonates of 0-28 days and children aged one month to 14 yearsin Pediatric Intensive Care Unit (PICU) of Sardjito Hospital.Hypoxemia and hyperoxemia were obtained by using NellcorRpulse oximetry, at the same time as blood gas analysis was obtainedas a gold standard.Results There were 240 neonates and 268 children enrolled inthis study. Pulse oximetry test with cut-off point 91% (neonates)and 90% (children) for detecting hypoxemia had sensitivity of81% and 80%, specificity of 79% and 95% positive predictivevalue of 54% and 82% negative predictive value of93% and 93%positive likelihood ratio of 3. 79 and 14.20 and negative likelihoodratio of0.25 and 0.24. Pulse oximetry test with cut-off point 95%(neonates) and 97% (children) for detecting hyperoxemia hadsensitivity of 7 8% and 81% specificity of 66% and 79%, positivepredictive value of77% and 76% negative predictive value of 66%and 83% positive likelihood ratio of 2.26 and 3.84 and negativelikelihood ratio of 0.34 and 0.24.Conclusion Pulse oximetry has a fairly good validity in detectinghypoxemia in neonates and children and in detecting hyperoxemiain children to however, it is not good enough to be used to detecthyperoxemia in neonates.